Preparation and Characterization of a Novel Skin Substitute. (10th August 2010) - Castagnoli, Carlotta; Fumagalli, Mara; Alotto, Daniela; Cambieri, Irene; Casarin, Stefania; Ostorero, Alessia; Casimiri, Raffaella; Germano, Patrizia; Pezzuto, Carla; Stella, Maurizio
Abstract : Autologous epidermal cell cultures (CEA) represent a possibility to treat extensive burn lesions, since they allow a significative surface expansion which cannot be achieved with other surgical techniques based on autologous grafting. Moreover currently available CEA preparations are difficult to handle and their take rate is unpredictable. This study aimed at producing and evaluating a new cutaneous biosubstitute made up of alloplastic acellular glycerolized dermis (AAGD) and CEA to overcome these difficulties. A procedure that maintained an intact basement membrane was developed, so as to promote adhesion and growth of CEA on AAGD. Keratinocytes were seeded onto AAGD and cultured up to 21 days. Viability tests and immunohistochemical analysis with specific markers were carried out at 7, 14, and 21 days, to evaluate keratinocyte adhesion, growth, and maturation. Our results support the hypothesis that this newly formed skin substitute could allow its permanent engraftment in clinical application.